Neuromuscular Recovery Is Prolonged After Immobilization or Superimposition of Inflammation With Immobilization Compared to Inflammation Alone: Data From a Preclinical Model. Issue 11 (November 2016) - Stäuble, Christiane G.; Helming, Marc; Martyn, J. A. Jeevendra; Blobner, Manfred; Fink, Heidrun
Abstract : Objectives: Recovery from ICU-acquired muscle weakness extends beyond hospital stay. We hypothesized that immobilization, more than inflammation, plays a prominent role in the delayed recovery from critical illness. Design: Prospective, randomized, controlled, experimental study. Setting: Animal laboratory, university hospital. Subjects: Male Sprague-Dawley rats. Interventions: Animals were divided to have one hind limb immobilized ( n = 129) or sham-immobilized ( n = 129) on day –12. After surgery, rats were further assigned to two subgroups. To induce inflammation, rats received three IV injections of Corynebacterium parvum on days –12, –8, and –4. Controls received saline at the respective time-points. At day 0, the limbs were remobilized and recovery from inflammation and/or immobilization was followed for 36 days. Measurements and Main Results: At day 0 and after 4, 12, or 36 days of recovery, maximum tetanic tension and tetanic fade (functional parameters = primary outcome variables) as well as nicotinic acetylcholine receptor expression, muscle mass, and histologic changes (structural parameters = secondary outcome variables) were measured. Impaired maximum tetanic tension, decreased tibialis muscle mass, and fiber diameter due to inflammation alone recovered by day 4. Tetanic fade was not affected by inflammation. Immobilization-induced loss of tibialis muscle mass, decreased fiber diameter, and tetanic fade did not return to normal until day 36, while maximum tetanic tension had recovered at that time. In the presence of inflammation and immobilization, the decrease in tibialis muscle mass, fiber diameter, and maximum tetanic tension, as well as decreased tetanic fade persisted until day 36. Up-regulation of nicotinic acetylcholine receptors normalized before day 4 following inflammation, but persisted until day 4 following immobilization. Conclusions: In our model, muscle function and structure recovered from inflammation within 4–12 days. Immobilization-induced neuromuscular changes, however, persisted even at day 36, especially if inflammation was concomitant.